Collaborative Governance Model in the Development of Coconut Shell Charcoal Downstreaming in Banyuasin Regency: JEL Classification: H83, O25, O35, Q01, R58 - Edhib Harits Anugrah; Dapot Pardamean Saragih; Zulfiani Zulfiani; Ilham Wahyudi (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This study examines the collaborative governance model for the downstream development of coconut shell charcoal in Banyuasin Regency from a Quadruple Helix perspective. It explores how government, academia, business, and the community collaborate to promote sustainable industrial development based on local resources. A descriptive qualitative approach was employed using secondary data from scientific literature, institutional documents, previous studies, and collaborative governance frameworks related to coconut shell charcoal downstreaming and the Quadruple Helix model. The findings indicate that effective downstream development depends on strong collaboration among multiple stakeholders with complementary roles. The government serves as a regulator, facilitator, and coordinator through policy support, institutional strengthening, and MSME empowerment. Academia contributes through research, technological innovation, training, and human resource development to enhance product quality and competitiveness. Businesses play a strategic role in production, product diversification, distribution, and market expansion, while local communities and farmer groups ensure a sustainable supply of raw materials and strengthen community-based economic activities. The study also highlights participation, communication, trust, transparency, and accountability as essential principles of successful collaboration. Furthermore, downstream processing increases the economic value of coconut waste, generates employment, improves local incomes, and supports environmental sustainability. These findings emphasize the importance of strengthening cross-sector collaboration, institutional coordination, innovation, and market access to accelerate green economic transformation and sustainable local industrial development in Banyuasin Regency.